California Supreme Court Justice Wiley Manuel Visits Office of Fresno County Counsel - Watkins, Howard::::::::: (1979)
Superior Court Judge Leonard Meyers, Justice Wiley Manuel, Superior Court Judge Hollis Best Office law library in Hall of Records building 3rd floor